2015
DOI: 10.18488/journal.1/2015.5.7/1.7.369.381
|View full text |Cite
|
Sign up to set email alerts
|

Study the Role of Customer-Based Brand Equity in the Brand Personality Effect on Purchase Intention

Abstract: In the Brand literature, few studies especially in Iran investigated the brand functions and business success. Hence, this study aims to provide the desirable model to creation and developing a deeper insight into the role of brand equity in the relationship between brand personality and customers purchase intention. The study statistical population consists of the whole Mellat Bank customers in Qazvin province, which used a questionnaire to collect data from them. In addition to, four hypotheses were announce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This means that brand equity has a positive mediating role which can improve the brand personality effect on the customers purchase intention. This result is in parallel with the findings of Hakkak et al (2015) study. Therefore, developing a positive brand personality based on the customer's minds can increase the customers' intention to use the brand and finally achieve a strong predictor of customer's behaviour.…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…This means that brand equity has a positive mediating role which can improve the brand personality effect on the customers purchase intention. This result is in parallel with the findings of Hakkak et al (2015) study. Therefore, developing a positive brand personality based on the customer's minds can increase the customers' intention to use the brand and finally achieve a strong predictor of customer's behaviour.…”
Section: Methodssupporting
confidence: 91%
“…Some studies confirm the positive effect of brand personality on the brand equity (Stephanie, Aaron, Lay Peng & Jayne, 2011;Gonçalves Santos, 2013;Hakkak et al, 2015). Stephanie et al (2011) in a study entitled "The Effect of Brand Personality and Congruity on Customer-based Brand Equity and Loyalty of Personal Computer Brands", confirmed the effect of brand personality on brand equity and showed that the emotional dimensions and competence in the brands of personal computers are very important.…”
Section: Brand Equitymentioning
confidence: 93%
See 2 more Smart Citations
“…This theory assumes an individual motive to perform behavior as a function of the attitude towards behavior in a certain situation; the norm that ruled behavior in a certain situation and motivation to follow these norms (subjective norm). TRA is very instrumental and practical where an individual personally responsible for purchasing motive [12] [13].…”
Section: Introductionmentioning
confidence: 99%